ANALISIS PERBANDINGAN PENERAPAN ESG ANTARA BANK SYARIAH DAN BANK KONVENSIONAL DI INDONESIA: SEBUAH ANALISIS EMPIRIS - Izzadieny, Fitra; Rizka, Nor Rahma; Ulfida, Deafatunnizwa; Hidhayati, Annisa Tri; Nadiar, Rahmi (UNIVERSITAS DHARMAWANGSA, 2025)
This study examines the differences in sustainability performance between Islamic and conventional banks in Indonesia using ESG (Environmental, Social, and Governance) scores as the leading indicator. The sample used was banking companies listed on the Indonesia Stock Exchange from 2022–2023, selected through purposive sampling. The analysis method used is multiple linear regression with dummy variables to differentiate between Islamic and conventional banks and Return on Assets (ROA) as a control variable. The analysis results indicate that Islamic banks have significantly lower ESG scores than conventional banks despite having higher financial performance (ROA). These findings suggest that sustainability values in Sharia principles have not been fully implemented in ESG practices. Based on Sustainability Theory and Stakeholder Theory, Islamic banks need to expand their sustainability focus beyond compliance with sharia law to include social responsibility, corporate governance, and environmental impact. This study contributes to developing ESG literature in the Islamic finance sector and provides insights for regulators and industry players in promoting more sustainable Islamic banking.